Study on the Preparation of the AOPAN/MMT Composite Nanofibers and Their Application for Laccase Immobilization. Issue 3 (September 2016) - Feng, Quan; Wu, Dingsheng; Huan, Shan; Li, Man; Li, Xin
In this paper, a novel nano-material was prepared, and then was applied for enzyme immobilization. Amidoxime ployarcylonitrile /montmorillonite (AOPAN/MMT) composite nanofibrous membranes were generated by electrospinning and amidoxime modification, then the nanofiber membranes were modified by glutaraldehyde; the modified AOPAN/MMT composite nanofibers were applied in laccase immobilization by adsorption and crosslinking method. Scanning electron microscopy was used to visualize the morphology of the nanofibers, and Fourier transform infrared spectroscopy was used to provide information on the surface chemistry of original and modified nanofibers. At the same time, the optimization of immobilization conditions and the relative properties of the immobilized laccase were also studied in this thesis. According to the experimental results the optimum conditions of laccase immobilization were obtained: glutaraldehyde concentration, crosslinking time, enzyme immobilization time were determined as 5%, 10 h and 12 h, respectively. The immobilized laccase showed a better stability resistance to temperature and pH change. Comparison of storage stabilities showed that the immobilized laccase retained more than 62.6% of its initial activity when stored at 4°C for 20 days. However, the free laccase lost most of its activity under the same conditions. The immobilized laccase retained 64.5% of its initial activity after 10 repeated batches of reaction.